22.6k views
1 vote
Differentiate... How to solve this type of problem? y = cos^2(x^2 + x^3)

User Troi
by
5.6k points

1 Answer

2 votes

Answer:


(d y)/(d x) = - (2 x + 3 x^(2) )sin2(x^(2) +x^(3))

Explanation:

Step(i):-

Given y = cos² (x² + x³) ....(i)

By using differentiation formulas

a)
(d)/(dx) (cosx) = -sinx

b)
(d)/(dx) (x^(n) ) = n x ^(n-1)

Step(ii):-

Differentiating equation (i) with respective to 'x'

First apply formula
(d)/(dx) (x^(n) ) = n x ^(n-1)


(d y)/(d x) = 2 cos (x^(2) +x^(3) )^(2-1) (d)/(d x) (cos(x^(2) +x^(3))

Now we will apply formula


(d)/(dx) (cosx) = -sinx


(d y)/(d x) = 2 cos (x^(2) +x^(3) ) (-sin(x^(2) +x^(3))(d)/(dx) (x^(2) +x^(3) )

Again apply formula
(d)/(dx) (x^(n) ) = n x ^(n-1)


(d y)/(d x) = 2 cos (x^(2) +x^(3) ) (-sin(x^(2) +x^(3)) (2 x + 3 x^(2) )


(d y)/(d x) = -2 sin (x^(2) +x^(3) ) cos(x^(2) +x^(3)) (2 x + 3 x^(2) )

we know that trigonometric formulas

Sin 2θ = 2 sinθ cosθ


(d y)/(d x) = -sin2(x^(2) +x^(3)) (2 x + 3 x^(2) )

Final answer:-


(d y)/(d x) = - (2 x + 3 x^(2) )sin2(x^(2) +x^(3))

User Denysonique
by
5.9k points